Therapy of reprogrammable immune activating supramolecular-based chitosan membranes for skin regeneration. (March 2023) - Chen, ShuRui; Gao, Jinpeng; Luo, Xiang; Sun, Yu; Jin, Wen; He, Rongrong
Graphical abstract: Highlights: Sol-CM shows sustained and H2 O2 -induced accelerated release of solamarine. Sol-CM exhibits anti-inflammation properties against M1 macrophages. Sol-CM develops into a permissive microenvironment characterized by proregenerative immune cell phenotypes and a substantially improved wound healing. Abstract: Immune cells play an important role in the inflammatory and proliferative stages of diabetes skin defect. How to regulate immune response is the key to skin regeneration. To address this challenge, we developed chitosan polymer membrane (CM) to directly deliver solamarine (Sol) for targeting reactive oxygen species (ROS)-enriched microenvironment. The Sol-loaded CM (Sol-CM) inhibits the excessive recruitment of inflammatory cells, and polarizes macrophages into an anti-inflammatory phenotype "M2″ to inhibit excessive inflammatory response. Therefore, the Sol-CM can help maintain immune homoeostasis, which contributes to the pathogenesis of wound. The Sol-CM demonstrated excellent therapeutic efficacy in treating wound. In addition, Sol-CM significantly attenuates focal inflammation and fibrosis level, thus potentially leading to a highly innovative and translational approach to treat diabetic wound efficiently and safely.